New records of Micropezidae (Diptera, Acalyptratae) from South Korea, with description of a new species of Rainieria Rondani - Kim, Wonwoong; van Der Weele, Ruud; Lee, Seunghwan (Zootaxa, 2022)
The stilt-legged fly (Diptera, Micropezidae) fauna of South Korea is reviewed, including a description of a new species, Rainieria tenebrosa Kim and Lee sp. nov., and 4 new distributional records (Micropezinae: Micropeza soosi Ozerov; Taeniapterinae: Rainieria triseta Li, Liu & Yang, Mimegralla suzukiana (Matsumura); Calobatinae: Compsobata dentigera (Loew)). Detailed information on the biology of the new species is presented. Keys to the Palearctic species of Rainieria and the Korean Micropezidae species are provided.